Restorative Transformation after Lockdown: Freedom and Ubuntu in Civic Education - Allsobrook, Chris; Ndlazi , Gugu (Phronimon, 2021)
We contend that lockdown restrictions to prevent the spread of Covid-19 in South Africa have exposed deep divisions between citizens and the state, due in part to the neglect of citizenship education and to the neglect of our historical citizenship heritage. We propose in this paper two sources of appropriate normative guidelines, rooted in our common, collective history and ethics, which we ought to promote among citizens to reunite our people. We argue that citizenship education ought not only to be promoted actively in schools but that it must be reformed on the basis of two sets of foundational principles: a) Ubuntu; and b) the Freedom Charter. These encourage integration between citizens and subjects, and between citizens and the state; not to impose false universality from above, nor incoherent heteronomy from below, but to regulate these with cultural and historical continuity in transformation.